Crafting Editorial Settlements - Eaves, Morris (Romanticism on the Net, 2006)
AbstractWilliam Blake's experimental artistic technologies produced a formidably complex artistic legacy. The Blake Archive (www.blakearchive.org) set out on a mission to restore that legacy by digital means—an ecological effort to reintegrate dispersed and disaggregated textual and pictorial fragments. But more than a decade of collective experience has revealed that the Archive is concerned at least as much with recapitulation and recycling as with restoration, and as much with disciplined fragmentation as with integration. The best explanation for the Archive's place in the posthumous history of Blake's work is in terms of editorial settlements that are crafted, negotiated, and imposed by editors acting as the agents of posterity. Those settlements are active participants in dynamic systems. Through three distinguishable historical phases—radical normalization in the decades following Blake's death; consolidation and institutionalization in the twentieth century; and, most recently, a digital superconsolidation that is simultaneously progressive and conservative—the editorial history of Blake's art elucidates several fundamental characteristics of editorial theory and practice. It also reveals suggestive symptoms of an unsettled and unsettling future of work, hope, challenge, and compromise on the brink of the known editorial universe.